Factors Affecting the Opinion of Rice Farmers in Pulau Hanaut District, Kab. East Waringin City - Andi Saputra (Fakultas Ekonomi dan Bisnis Universitas Palangka Raya, 2020)
This study aims to determine how big the influence of land area, selling price, production results and production costs on rice farmers' income both simultaneously and partially. The population in this study were all rice farmers in Pulau Hanaut District, Kab. Kotawaringin Timur, which amounted to 184 farmers and which was only used as a sample, amounted to 126 respondents using a non-probability sampling technique. Sources of data in this study are primary data and secondary data. The process of data analysis using classical assumption test, multiple regression analysis and hypothesis testing with the help of SPSS. The results of the instrument test show that the variables of land area (X1), selling price (X2), production yield (X3), and production costs (X4) simultaneously have a significant and positive effect on the income level of rice farmers in Pulau Hanaut District, Kab. East Kotawaringin.